ESTIMATION OF FOREST FIRE AREAS IN PALANGKA RAYA, CENTRAL KALIMANTAN, INDONESIA USING NBR2 AND ITS IMPACT ON ENVIRONMENT - Filsa Bioresita; Dennis Euro Pongdatu; Noorlaila Hayati; Udiana Wahyu Deviantari; Cherie Bhekti Pribadi (Indonesian Journal of Forestry Research, 2025)
Indonesia, particularly Palangka Raya City in Central Kalimantan, boasts approximately 241,736.25 hectares of forested areas crucial for human survival. Despite their significance, these areas are plagued by annual forest fires that lead to damage and adverse effects on the environment, including vegetation health and air quality. This research sought to pinpoint the extent of forest fire occurrences and their repercussions by analyzing changes in vegetation health and air quality through remote sensing technology. The study employed various remote sensing techniques, such as the Normalized Burn Ratio 2 (NBR2) for detecting burned areas, the Enhanced Vegetation Index (EVI) for assessing vegetation health, and PM2.5 for analyzing air quality. Utilizing Landsat-8 satellite imagery data as the primary source, the research successfully identified burned areas with an impressive overall accuracy of 82.229% using the NBR2 index. The findings revealed a direct correlation between forest fires and increased air pollution, particularly in PM2.5 levels, as well as a decline in vegetation health in the vicinity of the burned areas. These results highlight the importance of continuous monitoring of forest fire occurrences and their impact through remote sensing data to mitigate their adverse effects.